Extraction of Co(II) Spectrophotometrically by using Reagent 2-Acetyl Thiophene Thiocyanate - B. CHAUDHARY, AVINASH; S., NIRUPA; LOKHANDE, R.S. (Asian Journal of Chemistry, 2010)
2-Acetyl thiophene thiocyanate (ATT) was proposed as extractant for development of extractive spectrophotometric method for determination of Co(II). The reagent coordinates with Co(ll) to produce yellow coloured complex which was then extracted into ethyl acetate at pH 10.8-11.2 having absorption maxima at 450 nm. The thermal study showed that the extraction reactions are exothermic in nature with the reagent, and the stoichiometric ratio of Co(ll) to 2-acetyl thiophenethiocynate in organic phase was 1 : 2. The method permits separation and determination of cobalt from real and synthetic mixtures. The separation of Co(ll) from bivalent metal ions has also been studied.